Implementasi Sistem Rujukan Online pada berbagai Situasi Pelayanan Kesehatan : Sistematik Review - Suhadi Suhadi; Ruwiah Ruwiah; Wa Ode Salma (NHM PRESS, 2021)
The online referral system (eReferral) is designed to improve waiting times and efficiency by standardizing information and online communication in the referral process. Online referral is the automation of the referral process in which appointments and other information regarding the outcome of a consultation are transferred between two or more healthcare providers. This study was designed to identify the implementation of online referrals at various levels of health care. This systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. Of the 10 articles included in this review, 6 studies were conducted in the USA, 2 studies in Canada, and one each in the UK, and Saudi Arabia. The studies used a variety of designs, including Quasi-experimental (n=5), longitudinal (n=2), qualitative (n=1), and Research and Development (n=2). This study provides a clear picture of the use of an online referral system, starting from the work process, effectiveness, barriers, and development possibilities for a wider reach. This system is very helpful in easing the workload of specialist doctors and for patients who are referred users get the benefit of shorter waiting times/queues, making it possible to reduce medical costs further.